Estimation Planning for Building Wall Repair Due to Water Seepage: Case study of UMMU student flat building - Marsaoly, Irawati; Yusuf, Rais D. Hi.; Usamah, Muhammad (JURNAL BIOSAINSTEK, 2024)
The aims of this research are 1. To find out the factors that cause wall damage to student flats (rusunawa) at the Muhammadiyah University of Maluku Mtara. 2. To find out ways to repair wall damage due to seepage in student flats (rusunawa) at Muhammadiyah University, North Maluku. 3. To find out the estimated cost of repairing the walls of the student flats (rusunawa) at Muhammadiyah University, North Maluku. The type of research used in this research is a qualitative descriptive method. The qualitative method is a method of collecting data using observation, namely by examining an object by making observations about the situation, conditions and events that occur, so that the characteristics of the conditions of the research object can be clearly described according to the facts obtained. 1. Factors that cause damage to occur a. Mechanical Damage b. Physical Damage c. Chemical Damage d. Biological Damage e. Damage due to user factors 2. How to deal with damage to building walls a. Repair Using the Concrete Injection Method. The following is how to determine the right type of injection according to the condition of the damaged building. 1. Injection of cracked concrete structures (epoxy injection method) 2. Injection of leaking concrete (cement injection method) 3. Injection of damp concrete (polyurethane injection method) 4. Leak injection of pipe installation areas (cement injection method) b. Repairs Using Waterproofing 1. Using Waterproofing with a Membrane System 3. The total estimated cost of repairing the walls of the Flats Building (Rusunawa) Muhammadiyah University of North Maluku is IDR 708,843,000.00 (Seven Hundred Eight Million Eight Hundred Forty Three Thousand Rupiah).